An Empirical Study on the Integration of Culture &Tourism Industries and Its Impact on the Residents' Consumption Upgrading - Xiangwu Wang, Yulian Ding , (Design Engineering, 2020)
Based on the provincial panel data of culture & tourism industry from 2004 to 2017, this paper empirically tests the impact of culture & tourism industry integration on the residents' consumption upgrading and provides scientific basis for the deep integration of the two industries in China. On the basis of the calculation of integration degree of the two industries by coupling coordination degree model, it is found that Shaanxi Province has the highest integration level in culture & tourism industries, while Xinjiang has the lowest level of integration of culture and tourism. The level of integration of culture and tourism in central China is the highest in the regional level and the differences among provinces are marginal, followed by the eastern China and the western China, and the differences among provinces are significant. Through the empirical test on the impact of the two industries integration on residents' consumption upgrading by using autoregressive distribution lag model, it is found that the development of the two industries integration can significantly promote residents' consumption upgrading in the short and long term, but the long-term impact is significantly higher than the short-term impact. The most significant long-term impact is in eastern China, followed by the central and central China. The most significant short-term impact is in central China, followed by eastern and western China.